Genetic Evidence Supporting a Causal Role of Snoring in Erectile Dysfunction - Xiong, Yang; Zhong, Xin; Zhang, Fuxun; Wang, Wei; Zhang, Yangchang; Wu, Changjing; Qin, Feng; Yuan, Jiuhong (Frontiers in Endocrinology, 2022)
Background: The association between snoring and erectile dysfunction (ED) is inconsistent in multiple observational studies. To clarify the causal association of snoring on ED, we performed this two-sample Mendelian randomization (MR) study. Materials and Methods: The single nucleotide polymorphisms (SNPs) associated with snoring were retrieved from the UK biobank cohort with 314,449 participants (117,812 cases & 196,637 controls). The summary statistics of ED were obtained from the European ancestry with 223,805 subjects (6,175 cases & 217,630 controls). Single-variable MR and multivariable MR analyses were used to assess the causal relationship between snoring and ED. Results: Genetically predicted snoring increases the risk of ED (OR = 3.45, 95% CI = 1.68 - 7.09, P < 0.001) in the inverse variance weighting estimator. In sensitivity analyses, the ORs for the weighted median, MR. robust adjusted profile score, and MR Pleiotropy Residual Sum and Outlier approaches are 5.70 (95% CI = 1.19 - 27.21, P < 0.05), 3.14 (95% CI = 1.01 - 9.72, P < 0.05), and 3.11 (95% CI = 1.63 - 5.91, P < 0.01), respectively. No heterogeneity and pleiotropy are observed (P for MR-Egger intercept = 0.748; P for global test = 0.997; P for Cochran's Q statistics > 0.05). After adjusting for total cholesterol, triglyceride, low-density lipoprotein, and cigarette consumption, the ORs for genetically predicted ED are 5.75 (95% CI = 1.80 - 18.34, P < 0.01), 4.16 (95% CI = 1.10 - 15.81, P < 0.05), 5.50 (95% CI = 1.62 - 18.69, P < 0.01), and 2.74 (95% CI = 1.06 - 7.10, P < 0.05), respectively. Conclusion: This study provides genetic evidence supporting the causal role of snoring in ED.